HAEMATOLOGICAL STATUS DURING OESTRUS CYCLE IN REGULAR AND REPEAT BREEDING RED KANDHARI COWS - Shahpure, SN; Kekan, PM (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The results of the present study revealed that all haematological parameters (Hb,TEC,TLC, PCV ,Lymphocytes and Eosinophils ) were significantly (P
Keywords: Repeat breeder; Haematological parameters; Cows; Cattle